2017
DOI: 10.1371/journal.pone.0175942
|View full text |Cite
|
Sign up to set email alerts
|

Savanna elephant numbers are only a quarter of their expected values

Abstract: Savannas once constituted the range of many species that human encroachment has now reduced to a fraction of their former distribution. Many survive only in protected areas. Poaching reduces the savanna elephant, even where protected, likely to the detriment of savanna ecosystems. While resources go into estimating elephant populations, an ecological benchmark by which to assess counts is lacking. Knowing how many elephants there are and how many poachers kill is important, but on their own, such data lack con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 35 publications
(42 reference statements)
0
49
0
Order By: Relevance
“…Megafauna in general capture the problems of multispecies coexistence in the Anthropocene: Even with recognition of their ecological value, desires to conserve populations can conflict with available conservation land (139). The conservation statuses of many African megafauna are on a declining trajectory today (108,109), with rapid population declines in both megacarnivores (125,140) and megaherbivores (141,142). The threats include not only hunting (119,120), but also fencing and habitat destruction or fragmentation stemming from human activity (124,125,143).…”
Section: Anthropocene Challengesmentioning
confidence: 99%
“…Megafauna in general capture the problems of multispecies coexistence in the Anthropocene: Even with recognition of their ecological value, desires to conserve populations can conflict with available conservation land (139). The conservation statuses of many African megafauna are on a declining trajectory today (108,109), with rapid population declines in both megacarnivores (125,140) and megaherbivores (141,142). The threats include not only hunting (119,120), but also fencing and habitat destruction or fragmentation stemming from human activity (124,125,143).…”
Section: Anthropocene Challengesmentioning
confidence: 99%
“…Consequently, the densities at which carnivore populations occur naturally often remain unknown. Such estimates could be used to establish the ecological carrying capacity of populations (e.g., Hayward, O'Brien, & Kerley, ; Karanth, Nichols, Kumar, Link, & Hines, ), set conservation targets (e.g., Robson et al, ; Wikramanayake et al, ) and gain insight into the dynamics and determinants (i.e., by “top‐down” or “bottom‐up” processes) of carnivore populations in the absence of anthropogenic pressure (Wallach et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…), a young age structure, and densities much lower than those observed in some areas (Robson et al . ). The Mara elephant population has remained relatively stable in size during the past 15 years, with higher densities than the relatively unpopulated Serengeti (Figure A).…”
Section: Discussionmentioning
confidence: 97%
“…Examples of distributional shifts by elephants in response to human disturbances have been well-documented in other ecosystems (Douglas-Hamilton 1987;Graham et al 2009;Goheen and Palmer 2010). Nonetheless, the Serengeti and the Mara populations are undergoing a period of rapid in situ growth, evidenced by relatively low elephant carcass ratios compared to many ecosystems in Africa (Chase et al 2016), a young age structure, and densities much lower than those observed in some areas (Robson et al 2017). The Mara elephant population has remained relatively stable in size during the past 15 years, with higher densities than the relatively unpopulated Serengeti ( Figure 1A).…”
Section: Discussionmentioning
confidence: 97%